I died and was resurrected - Nyampinga, Hildegarde (Torture Journal, 2018)
I was born in 1974 in the Southern Province of Rwanda, where I grew up with my ten siblings. I moved after the genocide. Today, I live in Bugesera District, in the Eastern Province. My parents were killed during the 1994 genocide. Before they died, I had a very good life. The affection I was given by my aunt is the most pleasant thing I can remember from my life before the genocide. Since my aunt was also killed during the genocide, I cannot enjoy getting her affection anymore.